Evaluation of GPOvir Treatment in HIV-infected and AIDS Patients in Chai Nat Hospital - Wuttidechkamjorn, Naruephon (Journal of Health Science of Thailand, 2018)
A retrospective observational study was conducted in Chai Nat hospital in order to evaluate long-term efficacy of GPOvir as first line drug in HAART treatment in HIV-infected and AIDS patients from December 2003 to December 2006. It included a-year follow up after the treatment, with monitoring of CD4 cell count, liver function test and lipid profile at 0, 6 and 12 months. As a result, 84 local HIV-infected patients were enrolled. The most common adverse events were skin rash (13.7%) drug induced hepatitis (4.76 %) lipodystrophy (3.57%) peripheral neuropathy (10.7%) and dyslipidemia (10.7%). Post-treatment opportunistic infections were reported in 10.7 percent and 39 patients discontinued. The average CD4 cell counts at 0, 6 and 12 months were 45.72, 166.85 and 273.55 cell/mm3. In conclusion, GPOvir showed good efficacy without any serious side effects as an initial regimen for HIV-infeced patients in Thailand.